Better environment for development (UNDP New YorkUS, 1987)
Stresses the importance of a better global environment for development. Contains essays on desertification, soil conservation, reforestation, urban renewal, marine life, and pure water supply. Reviews UNDP's income and expenditure for the year 1986, discussing its follow-up investments and highlighting its new program developments and emergency activities. Summarizes projects carried out in several continents underlining their benefits to target populations.
IDS